2000
DOI: 10.1002/1097-4628(20001031)78:5<1009::aid-app100>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of low-density polyethylene- and linear low-density polyethylene-rich blends

Abstract: The crystallization of a series of low‐density polyethylene (LDPE)‐ and linear low‐density polyethylene (LLDPE)‐rich blends was examined using differential scanning calorimetry (DSC). DSC analysis after continuous slow cooling showed a broadening of the LLDPE melt peak and subsequent increase in the area of a second lower‐temperature peak with increasing concentration of LDPE. Melt endotherms following stepwise crystallization (thermal fractionation) detailed the effect of the addition of LDPE to LLDPE, showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
(39 reference statements)
1
20
0
1
Order By: Relevance
“…Given that the cast films are quenched more rapidly than the blown films, the LDPE and LLDPE phases do not have time to develop separate crystalline regions when quenched and therefore exhibit a broad melting endotherm and a higher level of co-crystallisation of the LLDPE and LDPE. This would tend to confirm the work by Drummond et al [13] who reported co-crystallisation occurring in blends of LLDPE and LDPE. However, the film tear properties shown in Figure 7 suggest a higher degree of orientation in the blown films compared to the cast films.…”
Section: Discussionsupporting
confidence: 88%
“…Given that the cast films are quenched more rapidly than the blown films, the LDPE and LLDPE phases do not have time to develop separate crystalline regions when quenched and therefore exhibit a broad melting endotherm and a higher level of co-crystallisation of the LLDPE and LDPE. This would tend to confirm the work by Drummond et al [13] who reported co-crystallisation occurring in blends of LLDPE and LDPE. However, the film tear properties shown in Figure 7 suggest a higher degree of orientation in the blown films compared to the cast films.…”
Section: Discussionsupporting
confidence: 88%
“…An alternative reason may be that EVOH does not interact with all parts of the polymer and therefore cancels out the positive reinforcement effects of the fibres, as described by Basson (2013). This was also highlighted by Drummond et al (2000) who stated that EVOH only facilitates interactions between the ethylene-rich areas of the LDPE and wood. The low and significantly different tensile strength of Beefwood composites with EVOH compatibiliser may also be caused by the high pH value of the wood, since the pH of wood affects a number of properties related to the quality of wood based composites (Hernández 2013).…”
Section: Tensile Strengthmentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8][9][10] and particularly in polyole fins; it helps in cost reduction and rising biodegrad ability of resultant composite as well as in increasing the rigidity (high modulus) [3] of the material. How ever, the starch concentration at which useful product can be obtained is therefore limited to a low range after which the materials properties suffer dramatically.…”
Section: Introductionmentioning
confidence: 99%